Effectiveness of Creative Instructional Multimedia on Students’ Motivation and Learning Styles - Putri Octa Hadiyanti; Yust Elida; Hidayatun Nur; Resy Oktadela (Jurnal Inovasi Pendidikan dan Sains, 2025)
This study aims to analyze the effectiveness of creative instructional multimedia in enhancing students’ learning motivation and to identify students’ learning styles in the Science and Social Science (IPAS) learning process at Sekolah Dasar Islam Plus of the Riau Islamic Education Foundation. The creative instructional multimedia used was based on visual, auditory, and kinesthetic modalities, with the expectation of accommodating differences in learning styles and increasing motivation. This study used a quasi-experimental method with a pretest-posttest control group design. The sample consisted of fourth-grade students selected through purposive sampling. The research instruments included a motivation questionnaire, a learning style test, observation sheets, and interview guidelines. The learning style test was conducted at the beginning of the study to identify students’ learning preferences to optimize the use of creative instructional multimedia according to each student's characteristics. This test was not repeated at the end of the study, as changes in learning styles are long-term in nature and influenced by multiple factors. Quantitative data were analyzed using descriptive and inferential statistics, including t-tests, while qualitative data from observations and interviews were analyzed using descriptive-qualitative techniques through data reduction, data display, and conclusion drawing. The results show an increase in motivation scores from 77.30% to 81.15% (a difference of 3.85%, p = 0.000), indicating a significant improvement. The multimedia also proves effective in facilitating various learning styles. These findings indicate that creative instructional multimedia enhances the learning motivation of elementary school students